ANALISIS ZAT GIZI DAN BIAYA SISA MAKANAN PADA PASIEN DENGAN MAKANAN BIASA - , Mihir Djamaluddin, Endy P Prawirohartono, Ira Paramastri ([Yogyakarta] : Fakultas Kehutanan UGM, 2005)
Background: The quality of food service in a hospital can be assessed from the inpatients' nutritional status. Food waste is an indicator of food service among inpatients. Besides its therapeutic value,food has asignificant economic value. The wasting cost in tenn of food waste affects the total availability of food costs. Objective: This study analyzes the nutrient quantity and the cost of food waste among inpatients with regular diet at Dr. Sardjito Hospital, Yogyakarta. Method: Thiswas a cross sectional study. The subjectswem inpatients aged 17 to 60 years old who got regular diet with length of stay was at least three days, and were willing to take part in this study (n=100). The amount of food waste was measumd using the Comstock visual estimation. The cost of food waste was calculated as the proportion of food waste from cost per serving. The quantity of nutrients in food waste was calculated using the Food Processor 2 softwam. The data were analyzed using Chi-square test. Results: There was a diffemnce of food waste according to gender. Rice waste was found more frequent among female (p&lt